2017
DOI: 10.17507/tpls.0707.14
|View full text |Cite
|
Sign up to set email alerts
|

Reading Comprehension Questions in EFL Textbooks and Learners’ Levels

Abstract: Abstract-This study investigated the reading comprehension questions in EFL textbooks and their appropriateness to learners' levels. The data for the study were collected from four elementary and advanced level EFL textbooks containing 44 chapters altogether. A checklist was designed based on Bloom's Taxonomy of reading comprehension questions to record the cognitive levels of the questions collected from the reading comprehension sections of the mentioned textbooks. To assess the significance of difference be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…The ndings rati ed those of previous studies (Adli & Mahmoudi, 2017;Roohani et al, 2014) which revealed the dominance of lower-order thinking skills in EFL textbooks. Nevertheless, the workbooks included more Content and Affect questions, a combination of lower-order and higher-order skills.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The ndings rati ed those of previous studies (Adli & Mahmoudi, 2017;Roohani et al, 2014) which revealed the dominance of lower-order thinking skills in EFL textbooks. Nevertheless, the workbooks included more Content and Affect questions, a combination of lower-order and higher-order skills.…”
Section: Discussionsupporting
confidence: 91%
“…In another study, Interchange Series (2005) was contrarily shown to include activities gearing to higher-order thinking skills (Razmjoo & Kazempourfard, 2012). Bloom's taxonomy was used to analyze the reading comprehension questions in elementary and advanced levels of two textbooks, American Headway and Inside Reading (Adli & Mahmoudi, 2017). The ndings were indicative of the dominance of the lower-order thinking skills.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cognitive order skills presented in this study stand for low-order cognitive skills (LOCS) and higher-order cognitive skills (HOCS). The former, as Adli & Mahmoudi (2017) refer to is the form of thinking that involves recalling and memorizing information, whereas the latter involves analysis, synthesis, and evaluation of conceptions and procedures. Thus, the higher cognitive skills (henceforth) higher-order thinking is an umbrella that incorporates creative thinking, critical thinking and problem solving.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the proportions of the questions may not be appropriate for their levels. A textbook written for elementary school students, for example, may have an excessive number of cognitively challenging questions [11].…”
Section: Introductionmentioning
confidence: 99%